RELIABILITY ANALYSIS OF TYPICAL COLD-FORMED STEEL BEAMS SECTIONS - Campos, Raylza Santos da Silva; Brandão, André Luis Riqueira; Rocha Freitas, Marcílio Sousa da (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This paper presents a reliability analysis of cold-formed steel beams, based on the FORM and MC simulation and using data obtained from experimental tests performed at the Johns Hopkins University, Baltimore (Schafer, 2003; 2006). This paper approached two sets of flexural tests, one referring to the failure by local buckling, and another for distortional buckling. A failure function is assembled to obtain, by taking into account the statistical parameters of the material (M), fabrication (F), and professional factors (P). The material and fabrication factors were taken from AISI standard. The professional factor was determined by comparing the tested failure loads and the predicted ultimate loads calculated from the selected design provisions. The goal of the paper is the assessment of reliability index for two nominal live-to-dead load ratios, as well as to compare the value found considering the load combinations for ultimate limit states.